SURVEILLANCE OF β-LACTAMASE GENES OF SALMONELLA FROM CHICKEN IN WET MARKETS OF METRO MANILA, PHILIPPINES - Miles Madayag; Rance Derrick Pavon; Jonah Feliza Mora; Khristine Balaga; Windell Rivera (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights - blaCTX-M gene in 24.7% while blaTEM gene in 11.2% of Salmonella isolates. - Coexistence of blaCTX-M groups II and IV in all blaCTX-M-positive isolates. - Dominance of blaCTX-M corroborated with phenotypic β-lactam resistances. - blaCTX-M-positive isolates had extended-spectrum β-lactamase and multidrug resistance.